Language Environment on Speaking Skills Training in Islamic Middle School - Maulana, Muhammad Rifqi; Ridha, Zein; Ahmed, Bakri Mohammed Bkheet (Institut Agama Islam Negeri Curup, 2024)
The aim of this research is to determine the language environment for speaking skills training at Al-Mumtaza Islamic Middle School, Banjarmasin. Speaking Arabic is not easy because it requires getting used to it. This School applies the Darul Lughoh system in Aceh for Arabic speaking training to make it easier to get used to speaking Arabic. However, there are problems in implementing the Darul Lughoh system in Aceh because not all students graduate from Islamic boarding schools. The research method used is narrative qualitative research. The subjects of this research are the principal and Arabic language teacher at this school. The object of this research is the language environment for speaking skills training at Al-Mumtaza Islamic Middle School. Data collection techniques using observation, interviews and documentation. Data analysis techniques with data reduction, data presentation and conclusions. Results: Al-Mumtaza Islamic Middle School adopted part of the language environment system from Darul Lughoh Aceh and implemented 2 language environments, namely a formal language environment and an informal language environment. A formal language environment is implemented in the classroom, namely in learning Arabic and learning religious knowledge. This school has a language preparation class for new students. Learning Arabic using the book al-Arabiyah Baina Yadaik. The informal language environment is implemented outside the classroom with several activities and programs including morning habituation, daily prayer repeating, vocabulary presentation, speeches, Arabic language camp, daily conversations, taqwa building night. This school has a special agency that monitors that students who do not use Arabic will be given warnings, punishments and even go to court.